2018
DOI: 10.5935/1518-0557.20180037
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on sperm banking: a Uruguayan experience

Abstract: ObjectiveThe purpose of this study was to investigate the status of homologous sperm banking in Uruguay.MethodsA retrospective investigation was performed on data collected between 2013 and 2015. Reasons for sperm banking, patient age, pre-freeze and post-thaw semen parameters, and recovery rates were analyzed.Results623 samples were cryobanked between 2013 and 2015. Only 324 samples were considered for analysis after selection based on inclusion criteria. In most cases the samples were stored because the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…It is common to find a reduction of up to 50% in viable cells after cryopreservation, even in fertile men (Vieira et al, 2012). Our post-thaw viability recovery rate (76%) is in agreement with values expected and reported in the literature (Counsel, Bellinge, & Burton, 2004;Ordoqui et al, 2018;Verheyen et al, 1993;World Health Organization, 2010). Upon analysing the total number of samples banked over the 28-year period, the results showed that the median of the sperm values were normal according to the WHO 2010…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is common to find a reduction of up to 50% in viable cells after cryopreservation, even in fertile men (Vieira et al, 2012). Our post-thaw viability recovery rate (76%) is in agreement with values expected and reported in the literature (Counsel, Bellinge, & Burton, 2004;Ordoqui et al, 2018;Verheyen et al, 1993;World Health Organization, 2010). Upon analysing the total number of samples banked over the 28-year period, the results showed that the median of the sperm values were normal according to the WHO 2010…”
Section: Discussionsupporting
confidence: 91%
“…Ejaculates were cryopreserved according to the standard protocol followed at Fertilab (Ordoqui et al, 2018). Briefly, semen samples were divided into two equal parts and washed in Earle's balance salt solution (EBSS) without HEPES by centrifugation (300 × g, 5 min).…”
Section: Semen Cryopreservationmentioning
confidence: 99%